2020
DOI: 10.1177/1524838020939126
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Children and Adolescents Survived Psychologically Traumatic Life Events: A Critical Review of Application of Resilience Assessment Tools for Clinical Referral and Intervention

Abstract: Psychological traumatic life events (TLEs) and resilience, both are multidimensional, complex, and share salient features. Both are products of individual, familial, and environmental (socio-cultural-political contextual) variables, which is very crucial in children and adolescents. This systematic review used Boolean search strategies in electronic databases, namely, PubMED, PsycNET, JStor, and Google scholar. All researches not studying resilience per se but similar or related constructs such as life strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…All population groups were considered for inclusion, regardless of how specific the study might have been with regards to age, occupation, socioeconomic status, or specific stressors to which individuals were exposed, as well as populations in both “normal” (i.e., non-treatment) circumstances and clinical settings. Moreover, this review was specifically concerned with studies that had explicitly considered the development, adaptation, or validation of a resilience measure in a novel context, in contrast to other reviews that have looked at the role of mixed methods studies of resilience more generally (Tol, Jordans, et al, 2013) or the psychometric properties of existing scales ( Satapathy et al, 2020 ; Windle et al, 2011 ; Zhou et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All population groups were considered for inclusion, regardless of how specific the study might have been with regards to age, occupation, socioeconomic status, or specific stressors to which individuals were exposed, as well as populations in both “normal” (i.e., non-treatment) circumstances and clinical settings. Moreover, this review was specifically concerned with studies that had explicitly considered the development, adaptation, or validation of a resilience measure in a novel context, in contrast to other reviews that have looked at the role of mixed methods studies of resilience more generally (Tol, Jordans, et al, 2013) or the psychometric properties of existing scales ( Satapathy et al, 2020 ; Windle et al, 2011 ; Zhou et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…A secondary aim of this review is to aggregate the PPFP of resilience identified across this collection of cross-cultural measures into a resource for investigators adapting a standardized measure. Although reviews of resilience measures have been conducted elsewhere ( Satapathy et al, 2020 ; Windle et al, 2011 ; Zhou et al, 2020 ), these have been primarily concerned with psychometric properties of measures, as opposed to their capacity for cross-cultural use and their ability to inform the development of context-sensitive scales with greater cultural relevance to the population of interest.…”
Section: Aims Of the Current Reviewmentioning
confidence: 99%
“…In accordance with this perspective, resilient individuals are capable of demonstrating sustained competence under stress. Resilience has also been conceptualized as a performance outcome of positive adaptation despite risk status, of recovery from trauma, or of overcoming negative multiple environmental threats and stressful experiences [26][27][28][29]. As the theoretical and empirical discourse has developed, resilience has been portrayed as a dynamic process encompassing positive adaptation.…”
Section: Risk and Resilience During Times Of Crisis And Disastermentioning
confidence: 99%
“…Nonetheless, several authors recommended increasing research on the effects of participation in trauma research [23,26,30,31,74,75,77,80,81,118,152] as well as educating IRBs on the possible benefits of trauma-focused research [23,77,80]. Articles on methodology concerned sampling and data collection [153][154][155][156], a need to use consistent measures and not conflate different constructs [123,127,128], a need to see participants as potentially being both survivors and perpetrators of violence [122], and the nocebo effect in trauma research [119]. Researchers offered recommendations on improving internal research validity when potential control group members with trauma do not identify themselves as having trauma [31,121], and many recommended using participatory research methods to conduct better research [132,135,137,138,155].…”
Section: Plos Onementioning
confidence: 99%